ENHANCEMENT OPERATION SYSTEM MODEL IN MANAGING LOCAL RESOURCES- BASED ENVIRONMENT TOWARDS SUSTAINABLE DEVELOPMENT - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This paper discussed at exploring an appropriate model in managing environment that may accommodate and optimize local resources, such as human resources and natural resources. This is important to create and maintain the sustainable development for all. In manifesting the sustainable development, this work found a new paradigm in sustainable development which is based on the local resources. In detail, it elaborates and discusses some core components of the model of sustainable development that includes: (i) ontology; (ii) epistemology; and (iii) axiology of sustainable development. The ontological element of sustainable development could be found in Pancasila, the principle five, that is social justice for all Indonesian constitution 1945, article 28 h that guarantee the healthy environment for all. While the epistemological level, this work will coherency all diametrical policies and norms or regulations that related to the situation, such as environmental law, investment law, mining law, agrarian law, forestry law, marine and coastal law, and so forth. All those elements should be embodied in the appropriate mechanism and operational model, that cover the implementation, control, evaluation, development and recovery stages. In the end, this work offers an appropriate model for creating local resources based-environmental management that guaranteeing the sustainable development for all